Synthesis, Characterization, and Photocatalytic Activities of Graphene Oxide/metal Oxides Nanocomposites: A Review - Jamjoum, Hayfa Alajilani Abraheem; Umar, Khalid; Adnan, Rohana; Razali, Mohd. R.; Mohamad Ibrahim, Mohamad Nasir (Frontiers in Chemistry, 2021)
Sustainable water processing techniques have been extensively investigated and are capable of improving water quality. Among the techniques, photocatalytic technology has shown great potential in recent years as a low cost, environmentally friendly and sustainable technology. However, the major challenge in the industrial development of photocatalyst technology is to develop an ideal photocatalyst which must have high photocatalytic activity, a large specific surface area, harvest sunlight and shows recyclability. Keeping these views, the present review highlighted the synthesis approaches of graphene/metal oxide nanocomposite, characterization techniques and their prominent applications in photocatalysis. Various parameters such as photocatalyst loading, structure of photocatalyst, temperature, pH effect of oxidizing species and wavelength of light were addressed which could affect the rate of degradation. Moreover, the formation of intermediates during photo-oxidation of organic pollutants using these photocatalysts are also discussed. The analysis concluded with a synopsis of the importance of graphene-based materials in pollutant removal. Finally, a brief overview of the problems and future approaches in the field is also presented.